Efficacy of autologous mesenchymal stem cell transplantation in patients with liver cirrhosis - Kantarcıoğlu, Murat; Demirci, Hakan; Avcu, Ferit; Karslıoğlu, Yıldırım; Babayiğit, Mustafa Alpaslan; Karaman, Bülent; Öztürk, Kadir; Gürel, Hasan; Akdoğan Kayhan, Meral; Kaçar, Sabite; Kubar, Ayhan; Öksüzoğlu, Gürol; et al. (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Because of several limitations and complications of liver transplantation, new alternative treatment modalities are required for patients with liver cirrhosis. Many study results encourage the use of autologous bone marrow-derived mesenchymal stem cells for liver diseases. In this study, we assessed the impact of autologous mesenchymal stem cell transplantation on liver tissue and liver chemistry. Materials and Methods: Twenty-five patients with biopsy-proven liver cirrhosis were enrolled in the study. Patients received 1×106 autologous mesenchymal stem cells/kg via a peripheral vein. Biochemical parameters were checked monthly. Periodical radiological screening and liver biopsies before mesenchymal stem cell transplantation were performed after 6 months. Liver specimens were assessed by a pathologist. Results: No side effect was observed and the mesenchymal stem cell transplantation procedure was well tolerated. Twelve patients completed the study. In 8 patients, improvements in Model for End-Stage Liver Disease (MELD) scores were observed. Serum albumin levels markedly increased in the third month. In patients with non-responder hepatitis C, HCV RNA levels both became negative after mesenchymal stem cell transplantation. Histopathological examinations of liver tissues before and at 6 months after transplantation revealed no change in liver tissue regeneration or fibrosis. However, in 5 patients, hepatitis activity index scores decreased. Conclusion: Autologous mesenchymal stem cell transplantation via peripheral vein is safe and feasible. Consecutive liver biopsy examinations suggested that mesenchymal stem cells could not reach the liver in a sufficient amount. Improvement in patients and clearance of HCV RNA may have occurred through immunomodulatory mediators secreted by transplanted mesenchymal stem cells, namely the “endocrine” effect.